Small bowel occlusion in the immediate postoperative period of total gastrectomy - Parodi, Hernán E.; Colet, Andrés; Praderi, Raúl C. (Cirugía del Uruguay, 1993)
Three patients who had undergone total gastrectomy presented occlusion of the small intestine in the postoperative which made it necessary to reoperate. In two cases gastric cancers had been resected and in the third one gastrectomy had been of necessity because of a bleeding juxta-cardial ulcer.